Building's rehabilitation towards sustainable behaviour - Silva, J.A.R. Mendes da (2010)
To achieve a sustainable building’s behaviour and preserve the environmental balance, three laws must be taken into account: (i) the resources’ consume must not be faster than the rate at which nature can restock them, (ii) the creation of systems that consume maximum energy-quality and (iii) the maximization of the use of renewable and recycled materials. Therefore, the buildings’ rehabilitation process must increase, instead of the proliferation of new buildings, in order to provide the sustainability of the built environment and minimize its ecological impact. The sustainable rehabilitation process is even more difficult in historical areas, in general sited in central zones of the urban mesh, with fragile comfort conditions and a rigid structure. In this paper, different evaluation tools for sustainable buildings were analysed in order to provide a set of evaluation criteria to be applied in the rehabilitation process in historical zones.